PERBANDINGAN PEMBELAJARAN KOOPERATIF TIPE STAD DAN NHT TERHADAP HASIL BELAJAR BIOLOGI - Herlina, Herlina; Oka, Anak Agung (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
The objectives in this research are : (1) To know whether is any difference the average of biology instructional by using model of cooperative learning STAD and NHT type. (2) To know which one more highÂ theÂ average of biology instructional by using model of cooperative learning STAD and NHT type.This research was conducted at the seventh grade of junior high school SMP N 1 Batanghari academic year 2011/2012. The sample of the reearch is VIIc and VIIE from five classes using cluster random sampling technique. From the hypothesis testing by using the formula of ttes, can be concluded that 1). There was any significant different the average of biology instructional by using model of cooperative learning STAD and NHT type. 2). The average of biology instructional between studentsâ learning using model of cooperative learning STAD more high from the average of biology instructional by using model of cooperative learning NHT.Based on the result of the research, the reseacher seggest to increase the instructional of studentsâ biology study about human organization material more effective using model of cooperative learning STAD type.Kata kunci: STAD, NHT, Hasil Belajar Biologi